New records of snakes (Squamata: Serpentes) from Dien Dien province - Dung, Le Trung; Hung Son, Nguyen Lan; Cuong, Pham The; Truong, Nguyen Quang (Academia Journal of Biology, 2015)
Based on a new herpetological collection from Muong Nhe Nature Reserve we added 13 new provincial records of snakes found in Dien Bien province, viz., Boiga cyanea, Dendrelaphis ngansonensis, Gonysoma prasinum, Lycodon futsingensis, Oligodon fasciolatus, Oreocryptophis porphyraceus, Rhabdophis nuchalis, R. subminiatus, Psammodynastes pulverulentus, Pareas carinatus, P. hamptoni, Pseudoxenodon macrops and Ovophis monticola. Our findings increase the species number of snakes to 46 in Dien Bien province